2022
DOI: 10.1007/978-3-031-15086-9_5
|View full text |Cite
|
Sign up to set email alerts
|

Omni-Channel Overtures Defining the Concept and Its Applicability in Public Sector Channel Management

Abstract: The channel landscape and citizens' channel behaviors are continuously evolving. This challenges how governments manage service delivery and their available service channels. To address these challenges, a new type of strategy has surfaced in the literature on private sector channel management; omnichannel management. But could the omni-channel concept be applied in the public sector context as well? More importantly: could it address the current challenges in the channel landscape? Currently no comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…Identifying transparency as the leading concern during the transformation towards an omnichannel strategy for public administration is a big leap towards establishing actionable guidance for managers and officials. Whereas the previous literature based on statistical data or broad surveys suggested that a potential solution to the problems of many public agencies or municipalities might be omnichannel (Rey-Moreno and Medina-Molina, 2016;Wirtz and Langer, 2017;Pieterson, 2017), this study points to an issue that needs special attention: transparency. Since this has been extensively studied in past literature (Bendoly et al, 2005;Barwitz and Maas, 2018;Quach et al, 2016;Nussbaumer et al, 2012a), it is possible to establish guidance for enhancing transparency by means of an omnichannel approach.…”
Section: Research Contributioncontrasting
confidence: 60%
See 4 more Smart Citations
“…Identifying transparency as the leading concern during the transformation towards an omnichannel strategy for public administration is a big leap towards establishing actionable guidance for managers and officials. Whereas the previous literature based on statistical data or broad surveys suggested that a potential solution to the problems of many public agencies or municipalities might be omnichannel (Rey-Moreno and Medina-Molina, 2016;Wirtz and Langer, 2017;Pieterson, 2017), this study points to an issue that needs special attention: transparency. Since this has been extensively studied in past literature (Bendoly et al, 2005;Barwitz and Maas, 2018;Quach et al, 2016;Nussbaumer et al, 2012a), it is possible to establish guidance for enhancing transparency by means of an omnichannel approach.…”
Section: Research Contributioncontrasting
confidence: 60%
“…ITP 37,2 directs the efforts providing a measurable quality for evaluation. Furthermore, because of its focus on a complex case (a building permit) and the consequent use of the citizen's perspective as the primary lens of analysis, this study complements previous insights which were based, primarily, on bird's-eye-view observations of channel choices and their usage (Rey-Moreno and Medina-Molina, 2016;Wirtz and Langer, 2017;Pieterson, 2017).…”
Section: Research Contributionmentioning
confidence: 76%
See 3 more Smart Citations